(-)-Epigallocatechin-3-gallate (EGCG) attenuates arsenic-induced cardiotoxicity in rats. (July 2016) - Sun, Tao-Li; Liu, Zhi; Qi, Zheng-Jun; Huang, Yong-Pan; Gao, Xiao-Qin; Zhang, Yan-Yan
Abstract: Chronic arsenic exposure in drinking water is associated with the abnormalities of cardiac tissue. Excessive generation of ROS induced by arsenic has a central role in arsenic-induced cardiotoxicity. (-)-Epigallocatechin-3-gallate (EGCG), the most abundant polyphenol in green tea, possesses a potent antioxidant capacity and exhibits extensive pharmacological activities. This study was aim to evaluate the effect of EGCG on arsenic-induced cardiotoxicity in vivo and in vitro. Treatment with NaAsO2 seriously affected the morphology and ultrastructure of myocardium, and induced cardiac injuries, oxidative stress, intracellular calcium accumulation and apoptosis in rats. In consistent with in vivo study, the injuries, oxidative stress and apoptosis were also observed in NaAsO2 -treated H9c2 cells. All of these effects induced by NaAsO2 were attenuated by EGCG. These results suggest EGCG could attenuate NaAsO2 -induced cardiotoxicity, and the mechanism may involve its potent antioxidant capacity. Highlights: (-)-Epigallocatechin-3-gallate (EGCG) attenuates arsenic-induced cardiotoxicity in vivo and in vitro. EGCG attenuates NaAsO2 -induced cardiac injuries, oxidative stress, intracellular calcium accumulation and apoptosis in rats. EGCG inhibits NaAsO2 -induced injuries, oxidative stress, and apoptosis in H9c2 cells.